EFFECT OF SCHOOL CLIMATE, WORK STRESS AND WORK MOTIVATION ON THE PERFORMANCE OF TEACHER - Sinaulan, Ramlani Lina (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
Performance is a form of behavior of a person or organization with achievement orientation. The study results are known (a) the school climate affect performance of teachers, b) there is influence of work stress on teacher performance, (c) work motivation effect on teacher performance, d) school climate influence on job motivation of teachers, and (e) work stress effect on work motivation of teachers. Suggestions studies (a) improving teacher performance should the top priority schools in school management efforts. This condition given that performance of teachers are the main pillars that determine the success of the school in improving quality of students. Therefore, performance of the teacher must always be good and necessary to update the knowledge of teachers on the latest information in education as benchmarks increase teacher performance, (b) job motivation of teachers needs to improved, among others, with reward and punishment impartial towards the success achieved by the teacher as well as the violations committed so that it becomes part of an effort to motivate teachers to work.